No effect of exercise on AD‐related cognition in older African Americans: Program for African American Cognition and Exercise (PAACE). (31st December 2021) - Carmichael, Owen T; Gwizdala, Kathryn L.; Brouillette, Robert; Beyl, Robbie; Johnson, William; Hebert, Callie; Carter, Leah; Harris, Melissa; Newton, Robert L
Abstract: Background: Lower levels of physical activity (PA) are associated with greater risk of cognitive decline and AD, and some studies suggest that interventions that increase PA engagement lower risk of cognitive decline and AD. However, interventions to date have largely not included substantial representation of African Americans. Method: The Program for African American Cognition and Exercise (PAACE) randomized 56 sedentary African American adults in the Baton Rouge, Louisiana area (mean age ± s.d.: 69.2 ± 3.4 years) to a physical activity group (PAG) or successful aging group (SAG). The PAG aimed to increase moderate to vigorous PA to national guideline levels over 12 weeks by providing supervised PA 2 days per week (90‐120 minutes/week) at local YMCAs along with 30‐60 minutes/week of home‐based PA. The SAG completed one 60‐minute educational session on successful aging per week for 12 weeks. The Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) was assessed before and after the intervention. ANOVA models assessed pre‐ to post‐intervention RBANS total scale and sub‐scale score changes, as well as differences between PA and control arms in these changes. Result: Groups were well matched by age, sex, BMI, employment, education, and income. The SAG increased scores on the RBANS overall scale and scales of visuospatial function, immediate memory, and delayed memory, along with the story memory, figure copying, coding, and figure recall sub‐scales (all p<.05). The PAG increased scores on only the list learning sub‐scale (p=.047). Scores on the overall scale (p=.034) and story memory sub‐scale (p=.0008) increased significantly more in the SAG than in the PAG. No RBANS scores increased significantly more in the PAG compared to the SAG. Conclusion: A 12‐week PA promotion program among community‐dwelling older African American adults provided significant cognitive benefits to an educational control group, and minimal benefits to those engaged in PA. Possible contributors to these results include inadequate PA stimulus in the PAG, and beneficial health behavior changes or cognitive stimulation in the SAG. Future research is needed to fully understand cognitive effects of PA interventions among older African Americans.